Spectroscopic evidence for two-gap superconductivity in the quasi-1D chalcogenide Nb2Pd0.81S5. (26th March 2018) - Park, Eunsung; Lee, Sangyun; Ronning, Filip; Thompson, Joe D; Zhang, Qiu; Balicas, Luis; Lu, Xin; Park, Tuson
Abstract: Low-dimensional electronic systems with confined electronic wave functions have attracted interest due to their propensity toward novel quantum phases and their use in wide range of nanotechnologies. The newly discovered chalcogenide Nb2 PdS5 possesses a quasi-one-dimensional electronic structure and becomes superconducting. Here, we report spectroscopic evidence for two-band superconductivity, where soft point-contact spectroscopic measurements in the superconducting (SC) state reveal Andreev reflection in the differential conductance G . Multiple peaks in G are observed at 1.8 K and explained by the two-band Blonder–Tinkham–Klapwijk model with two gaps Δ1 = 0.61 meV and Δ2 = 1.20 meV. The progressive evolution of G with temperature and magnetic field corroborates the multiple nature of the SC gaps.